[Sparing no one; PLDT 2 ; Rowing [videorecording] - Lazaro, Cheche (Quezon City Probe Productions, 1993)
A look at Manila as one of twenty most polluted cities in the world and one of the seven most polluted in Asia. The public's clamor for changes on PLDT, a Cojuangco-controlled operations of the country's largest monopoly. Dragon boat racing, a water sport hits Manila Bay.
Contents : Sparing no one (20 min.) -- PLDT 2 (14 min.) -- Rowing (11 min.).
VHS
Keywords: Philippine Long Distance Telephone Company; Air pollution -- Environmental aspects. -- Philippines -- Manila Metropolitan area; Rowing -- Philippines; Telephone systems -- Philippines